Modelo de sustitución de las importaciones de medicamentos de marca (Ocam Protect; Simepar) por la producción nacional de medicamentos genéricos de uso humano y su respectiva distribución a través del Sistema de Salud Pública del Ecuador - Alban Paz, Adriana Sofía (2015)
This project is framed within the change initiatives of the national production model promoted by the Government, since it seeks through this study to develop a marketing company of generic drugs, not controlled, produced in Ecuador and of local intensive usage, using this strategy it is proposed to compete with trademarks like SIMEPAR and OCAM PROTECT (both imported) whose active ingredients are free from patent and therefore may be reproduced generically. In this context, the local market for the drugs listed were investigated, determining an important business opportunity in a market with a growing unmet demand, to take advantage of this environment, the association was established as a strategy with local generic producing companies, by which the product will be obtained and sales strategies were developed via medical visit to promote the prescription of generic massive buying in hospitals through public purchasing system; These procedures allowed for an estimated financial study through which was found that the success of marketing initiatives proposals would generate a financially viable enterprise in the medium term. It should be clarified that as part of the project an image and business philosophy to promote sales was designed, including the processes related to pricing and costs authorized production, always framed within legal limits existing sales processes and consumption of generic drugs nationwide